Vandermonde determinantal ideals - Watanabe, Junzo; Yanagawa, Kohji (MATHEMATICA SCANDINAVICA, 2019)
We show that the ideal generated by maximal minors (i.e., $k+1$-minors) of a $(k+1) × n$ Vandermonde matrix is radical and Cohen-Macaulay. Note that this ideal is generated by all Specht polynomials with shape $(n-k,1, …,1)$.